Management of Solitary 1 cm to 2 cm Liver Nodules in Patients with Compensated Cirrhosis: A Decision Analysis - Karen E Bremner; Ahmed M Bayoumi; Morris Sherman; Murray D Krahn (Canadian Journal of Gastroenterology)
OBJECTIVES: Current guidelines, based on expert opinion, recommend that suspected 1 cm to 2 cm hepatocellular carcinoma (HCC) detected on screening be biopsied and, if positive, treated (eg, resection or transplantation). Alternative strategies are immediate treatment or observation until disease progression occurs.